Trinidad and Tobago, British West Indies - (:unkn) unknown (Reproduced and printed by the Litho Section, LAS Dept.,[Tirnidad and Tobago], 2011)
Desccription printed on the back of the postcard: "This map shows principal places of interest, sport, beautiful drives and bathing beaches that the thousands of tourists who visit these lovely islands each year are able to enjoy."
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Maps; Trinidad and Tobago